Tailoring morphology and size of microstructure and tensile properties of Sn-5.5 wt.%Sb-1 wt.%(Cu,Ag) solder alloys - Dias, Marcelino (2021)
Transient directional solidification experiments, and further optical and scanning electron microscopy analyses and tensile tests, allowed the dependence of tensile properties on the micromorphology and length scale of the dendritic/cellular matrix of ternary Sn-5.5Sb-1Ag and Sn-5.5Sb-1Cu alloys to be determined. Extensive ranges of cooling rates were obtained, which permitted specific values of cooling rate for each sample examined along the length of the casting to be attributed. Very broad microstructural length scales were revealed as well as the presence of either cells or dendrites for the Ag-containing alloy. Hereafter, microstructural spacing values such as the cellular spacing, λ c, and the primary dendritic spacing, λ 1, may be correlated with thermal solidification parameters, that is, the cooling rate and the growth rate. While, for the Cu-containing Sn-Sb alloy, the β-Sn matrix is characterized only by the presence of dendritic arrangements, the Ag-containing Sn-Sb alloy is shown to have high-velocity β-Sn cells associated with high cooling rate regions, i.e., positions closer to the bottom of the alloy casting, with the remaining positions being characterized by a complex growth of β-Sn dendrites. Minor additions of Cu and Ag increase both the yield and ultimate tensile strengths when compared with the corresponding values of the binary Sn-5.5Sb alloy, with a small reduction in ductility. This has been attributed to the homogeneous distribution of the Ag3Sn and Cu6Sn5 intermetallic particles related to smaller λ 1 characterizing the dendritic zones of the ternary Sn-Sb-(Cu,Ag) alloys. In addition, the Ag-modified Sn-Sb alloy exhibited an initial wetting angle consistent with that characterizing the binary Sn-5.5Sb alloy